The Role of North Aceh Government for Building Women's Capacity Based on Islamic Values in Vocational Village - Malahayati Malahayati; Laila M Rasyid (Justicia Islamica, 2021)
Women have potential contributions to engage in productive activities and can help the family economy. A vocational village is a village setting a model for developing its local resources to improve inhabitants' quality of life, especially women in the village in North Aceh District, without leaving their Islamic values. This article described the role of government in enhancing women's capacity and local potential in the vocational village with Islamic values using the empirical methodology. Data is obtained based on field research through purposive sampling collected by interviews with informants using qualitative analysis data. This study found that several training initiatives had been carried out to increase women's capacity, such as training in embroidery, handicrafts, etc. However, these initiatives were not based on the potential components that live in the village. Furthermore, Islamic values in the community in encouraging women in North Aceh have experienced a shift in Pande Village. This study recommends more efforts to increase women's potential by promoting and exhibiting local products for empowering women in villages based on existing prospects without leaving Islamic values.